Investigating the performance of Tin-based perovskite solar cell with Cadmium Sulphide as etm and graphene as htm using SCAPS-1D - Owolabi, Adeyemi Joshua; Ali, Haruna; N Ukorah, Ijeoma; Onimisi, M.Y.; Tafida, R.A.; Awujoola, J. Olalekan; Gambo, Hassan (Physics and Chemistry of Solid State, 2024)
Solar cells based on lead-free perovskite have demonstrated great potential for renewable energy. The SCAPS-1D simulation software was used in this study to perform device modelling of a lead-free perovskite solar cell of the architecture Glass/FTO/CdS/CH3NH3SnI3/Graphene/Pt. For the performance evaluation, an optimization process of the different parameters such as thickness of the ETM, Absorber, Bandgap energy of the hole transport material was conducted. Extensive discussion on its effect on the performance of the solar cell parameters were stated. An optimal ETM and Absorber layer thickness was achieved at 40nm and 950nm. The Bandgap energy gave an optimal performance of device parameters at 0.9eV. Temperature variations were simulated and it was noted that the device had a minimal decrease in PSC parameters performance with increasing temperature. The final optimized device structure achieved a PCE, Voc, Jsc and FF of 25.65%, 0.9606 V, 33.2491(mA/cm2), and 80.32% respectively. Therefore, we expect that our findings will pave the way for the development of lead-free and highly effective perovskite solar cells.